Water moments for urban drainage projects and Nature-based solutions - Sandre, Adriana Afonso; Sant'Anna, Camila Gomes; Ayres, Carmen; Souza , Mariana Stoppa Ferreira de; Pellegrino , Paulo Renato Mesquita; Campos, Raul Moura (Latin American Journal of the Built Environment & Sustainability, 2025)
Objective – This paper aims to present the “Water Moments” method as a tool to guide the selection and sequencing of Nature-based Solutions (NbS) in urban drainage of landscape planning, applying it to the case of the Butantã Campus of the University of São Paulo. Methodology – The research adopts a theoretical-applied approach, grounded in the geomorphological compartmentalization proposed by Schutzer (2012) and developed by Bonzi (2015), combined with the hydrological reading of the urban water cycle. Maps of altimetry, slope, soil, land use, drainage networks and flood-prone areas were used to classify the territory into three moments: Source, Conduction, and Accommodation. Originality/relevance – The study addresses the gap between hydrological theory and design practice, proposing a method that integrates geomorphology, hydrology, and green infrastructure, providing clear parameters for the location of NbS in complex urban contexts. Results – The application of the method in the Butantã Campus demonstrated the feasibility of structuring distributed and multifunctional drainage networks, capable of reducing flood risks, enhancing groundwater recharge, and qualifying open spaces in the landscapes. Theoretical/methodological contributions – The article systematizes a replicable methodological framework that correlates watershed compartments with specific NbS, forming a combinatory planning tool based on water moments. Social and environmental contributions – The study highlights the potential of NbS to foster urban resilience, improve environmental quality, and provide multiple social, cultural, and educational benefits, positioning the campus as a living lab for sustainable drainage innovation and landscape.